2010
DOI: 10.1039/c0dt00325e
|View full text |Cite
|
Sign up to set email alerts
|

Cations in control: crystal engineering polyoxometalate clusters using cation directed self-assembly

Abstract: The synthetic engineering of anionic polyoxometalate (POM) clusters with predefined properties tailored to specific applications is a great challenge using routine "one-pot" POM syntheses. Under such conditions, difficulties often arise from the multitude of complex reaction pathways and self-assembly processes occurring in solution. In this respect the major role of the charge balancing cations cannot be ignored, in fact such cations are crucial, both in the assembly of the building blocks, linkage to the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 128 publications
0
86
0
3
Order By: Relevance
“…This kind of study relates to a special class of compounds: POM-based supramolecular assembles. This study allows us to better understanding the important role of cations on the formation of the POM anionic frameworks as structure directing agents [23][24][25] and on the control of catalytic activity of POM clusters [26][27][28].…”
mentioning
confidence: 99%
“…This kind of study relates to a special class of compounds: POM-based supramolecular assembles. This study allows us to better understanding the important role of cations on the formation of the POM anionic frameworks as structure directing agents [23][24][25] and on the control of catalytic activity of POM clusters [26][27][28].…”
mentioning
confidence: 99%
“…While the role of this cation is currently unclear, it is likely a combination of electrostatic, hydrogen bonding (via ‐OH and ‐NH groups) and possibly even coordinative interactions (via ‐OH groups) could stabilize reactive fragments and lead to {KW 36 } formation. In later studies, the authors also showed that replacing the K + with larger alkali and alkaline earth metals, and other ammonium or primary organo‐ammonium groups is also possible, opening the door to organo‐functionalized species …”
Section: Emerging Areas and Perspectivesmentioning
confidence: 99%
“…Equivalent reactions indicate that no crystals could be obtained without 1,6-diaminylhexane. Usually, rigid amines induced the formation of layered arrangements, whereas structurally more flexible amines resulted in formation of polymeric chains [28]. In this paper, we focus on the influence of pH and transition metals.…”
Section: Synthesismentioning
confidence: 99%